Toxicodendron succedaneum (L.) Kuntze (Japanese wax tree): A review on its phytochemistry, pharmacology, and toxicity - Shailendra S. Gurav; Charmaine Dias; Nilambari S. Gurav; Sameer J. Nadaf; Muniappan Ayyanar (Pharmaceutical Sciences Asia, 2022)
Toxicodendron succedaneum (L.) Kuntze (Anacardiaceae) is a deciduous tree widely distributed in South and Southeast Asia. The resin of T. succedaneum is used in decorating traditional handicrafts, and resinous latex is poisonous. The plant yields a commercially important wax and treats asthma, cough, fever, ear infections, pulmonary infections, diarrhoea, dysentery, nose bleeding, and liver disorders. The scientific literature on T. succedaneum was collected from Scopus, PubMed, and Google Scholar. Major bioactive compounds reported in the plant are urushiols, bichalcones, biflavonoids such as succedaneaflavanone, agathisflavone, rhusflavanone, amentoflavone, cupressuflavone, robustaflavone, volkensiflavone, morelloflavone, and hinokiflavone. In-vitro studies have demonstrated the antioxidant, antibacterial, antitumor, and antileukemic activities of T. succedaneum, supporting the rationale behind its traditional use. Biflavonoids exhibited a strong antiviral effect by inhibiting the replication of HIV, HBV, and HSV. However, with the presence of hinokiflavone and a skin-irritating oil (urushiol), the plant causes severe allergies in humans, which urges to standardize the effectiveness of this species. The available literature on T. succedaneum suggests insufficient data on pharmacological studies in experimental animals. Much research needs to be done to confirm its folk medicinal uses for developing phytopharmaceutical drugs.